Monetary Policy in Uncertain Times: ECB Monetary Policy Since June 2014. (11th October 2017) - Hutchinson, John; Smets, Frank
Abstract : The euro area economy is emerging from a very pronounced crisis which has added complexity to achieving the price stability objective. The ECB has implemented an array of monetary policy instruments which are working their way through the economy and are proving to be very effective in supporting the recovery. By acting as it has, the ECB has continued to show that it will always respond to its communicated reaction function and thereby, reassure the public of its commitment to its fulfilling its mandate.